The Influence of Technology in Wayang Golek Purwa Performances: Combining Tradition and Innovation - Maulana, Marsel Ridky; Karyono, Tri; Sunaryo, Ayo (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2024)
Wayang Golek Purwa, as one of the traditional cultural heritages of the Sundanese community, faces significant challenges in maintaining its existence amid the rapid development of modern technology. This research aims to analyze the influence of technology on Wayang Golek Purwa performances, especially in integrating tradition and innovation to attract a wider audience and be relevant to the digital era. This research uses a descriptive qualitative approach through direct observation, literature study, and audio-visual analysis of the performance. The findings show that the application of technology, such as visual projection, modern lighting, and digital sound, significantly enriches the aesthetic and dramatic dimensions of Wayang Golek Purwa. In addition, the integration of multimedia technology opens up new opportunities to introduce stories and characters that are relevant to the younger generation. However, the research also identified challenges, including limited access to technology among performers in rural areas. The fusion of tradition and innovation through technology opens up opportunities for the preservation of Wayang Golek Purwa while strengthening its appeal in the era of globalization. Recommendations are made to develop a model of collaboration between traditional artists and technology experts to maintain a balance between modernization and preservation of traditional values.